Development of Bedroom Interior Design Application Using Augmented Reality Technology - Purwandi, Ummi Athirah Binti; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2022)
Room interior design application is a platform used by users to better plan the purchase of furniture using augmented reality technology. Most equivalent applications do not have a specific category, the options provided are very limited where a fee will be charged to get premium access and furniture is not labeled name and price. The objective of this project is to design and develop applications that use mobile device-based 3D methods and subsequently test the functionality of the applications on target users. In developing this application, the process model used is Agile which consists of five phases including needs analysis phase, design, implementation, testing and deployment because it can be changed at any time according to the suitability of the project developed. The app was designed to identify the room floor surroundings to display furniture virtually using marker-less AR. The results obtained from the user acceptance test get a total of 89.57% where if the percentage is evaluated using the System Usability Scale (SUS) score scale, it is at an acceptable level. Overall, the built-in applications can be classified as applications that successfully meet the needs of the target users.